Pediatric liver transplant for maple syrup urine disease a single center experience - Hassan, Ibrahim; Mahjoub, Samah; Jalodi, Bushra; Khan, Iftikhar; Zidan, Ahmed; Tawfeeq, Mansour; Al Qahtani, Mohammed; Bader, Razan; Gadour, Eyad (Frontiers in Pediatrics, 2025)
IntroductionMaple syrup urine disease (MSUD) is an autosomal recessive inborn error of branched-chain amino acid metabolism caused by an inherited deficiency of branched-chain alpha-ketoacid dehydrogenase (BCKDH) activity that degrades isoleucine, leucine, and valine. Liver transplantation (LT) is a therapeutic option to treat the classical severe type of MSUD. This study aimed to assess and compare liver biochemical outcomes and amino BCAAs levels post-LT according to different types of donors.MethodsRetrospective cohort analysis of 10 patient medical records diagnosed as MSUD who underwent LT in King Fahad Specialist Hospital-Dammam between January 2013 and May 2023.ResultsTen pediatric patients diagnosed with MSUD who had finished 1 year of follow-up after LT were included in the study. The median age of diagnosis among the pediatric patients was 1 month (as it is included in the national neonatal screening). Besides, the median age for LT was 123 months (10 years 3 months) (with a range of 9–173 months). Availability of milk formula, prevention of further neurological insult, and difficulty in controlling the protein intake were the main indications for LT. Post LT, six patients (60%) were immediately initiated on a regular diet, and four patients (40%) waited for 3 months before starting a regular diet. All the patients were on Tacrolimus as immunosuppression, with three patients started on Mycophenolate because of biopsy-proven acute cellular rejection. Our result showed 100% 1-year graft survival and 100% until the time of report, with no donor complications. 70% of the explanted liver had been re-transplanted as a domino liver transplant. No clinical or laboratory difference when comparing living-related to living-unrelated or deceased donor liver transplant. 100% of our patients and families showed satisfaction with the decision of liver transplant.ConclusionMSUD post liver transplant showed a 100% graft survival rate, and all patients and families showed satisfaction. In settings with limited deceased donor organs, living-related donor LT (even from heterozygous carriers) is a viable option for MSUD, yielding comparable metabolic control and graft outcomes to other donor types.